Stress fiber strain is zero in normal aortic smooth muscle, elevated in hypertensive stretch, and minimal in wall thickening rats - Shukei Sugita; Rintaro Kawai; Yoshihiro Ujihara; Masanori Nakamura (Scientific Reports)
Abstract Hypertension causes aortic wall thickening until the original wall stress is restored. We hypothesized that this regulation involves stress fiber (SF) tension transmission to the nucleus in smooth muscle cells (SMCs) and investigated the strain in the SF direction as a condition required for this transmission. Thoracic aortas from Wistar Kyoto (WKY) and spontaneously hypertensive rats (SHRs) were examined. SFs in aortic SMCs were fluorescently labeled and observed under a confocal microscope while stretched along the circumferential (θ) axis. Three conditions were studied: WKY physiological (WKYphys; blood pressure changes from diastolic to systolic for WKY), high-strain state (WKYhigh; diastolic to hypertensive level for WKY simulating initial hypertension), and SHR physiological (SHRphys; diastolic to systolic for SHR simulating after wall-thickening). SF strain and direction were measured. The SF inclination angle from the θ axis was 18° ± 3° in WKYphys, 13° ± 2° in WKYhigh, and 20° ± 1° in SHRphys. SF strain was 0.01 ± 0.02 in WKYphys, 0.20 ± 0.04 in WKYhigh, and 0.02 ± 0.02 SHRphys. SF strain was minimal in WKYphys, significantly increased in WKYhigh, and reduced to approximately zero in SHRphys. These findings support SFs function as mechanosensors in response to hypertension.